High-performance triboelectric nanogenerator with double-surface shape-complementary microstructures prepared by using simple sandpaper templates - Zhang, Xu-Wu (2019)
The triboelectric nanogenerator (TENG), based on triboelectrification and electrostatic induction, has been proven to be an ideal power supply device which converts all kinds of mechanical energy into electrical energy. However, high cost of fabrication and modification prevents wide application. In this work, we demonstrated a simple, cost-effective but efficient method, in which the friction pair materials, i.e., copper electrode and polydimethylsiloxane (PDMS), were both patterned by using sandpaper templates. The copper electrode and PDMS were patterned with sandpaper-like morphology and sandpaper-complementary-like morphology, respectively. Compared with TENG devices with nonpatterned or single-sided patterned friction layer, TENG devices with two-sided patterned friction layers have better output properties when the sandpaper templates used for the PDMS and copper electrode have the same large grit sizes (above 2000) because of closer contact and more sufficient friction. When the sandpaper templates used for the PDMS and copper electrode have the same grit size of 10 000, the maximum output short-circuit current density, open-circuit voltage, transfer charge quantity, and power density of as-prepared TENG devices are 3.89 mA/m2, 200 V, 76 nC, and 4.36 W/m2, respectively. Overall, patterning microstructure morphology and corresponding complementary morphology on the respective two sides of friction pair shows efficient improvement for the performance of the TENG device, providing a good guidance for its modification.